Incidence, mortality, and survival of hematological malignancies in Northern Italian patients: an update to 2020 - Mangone, Lucia; Penna, Domenico; Marinelli, Francesco; Roncaglia, Francesca; Bisceglia, Isabella; Merli, Francesco; Ruffini, Alessia; Gamberi, Barbara; Tieghi, Alessia; Valli, Riccardo; Albertazzi, Laura; Iori, Mauro; et al. (Frontiers in Oncology, 2023)
Background Hematological malignancies (HMs) represent a heterogeneous group of diseases with diverse etiology, pathogenesis, and prognosis. HMs' accurate registration by Cancer Registries (CRs) is hampered by the progressive de-hospitalization of patients and the transition to molecular rather than microscopic diagnosis. Material and Methods A dedicated software capable of automatically identifying suspected HMs cases by combining several databases was adopted by Reggio Emilia Province CR (RE-CR). Besides pathological reports, hospital discharge archives, and mortality records, RE-CR retrieved information from general and biomolecular laboratories. Incidence, mortality, and 5-year relative survival (RS) reported according to age, sex, and 4 HMs’ main categories, were noted. Results Overall, 7,578 HM cases were diagnosed from 1996 to 2020 by RE-CR. HMs were more common in males and older patients, except for Hodgkin Lymphoma and Follicular Lymphoma (FL). Incidence showed a significant increase for FL (annual percent change (APC)=3.0), Myeloproliferative Neoplasms (MPN) in the first period (APC=6.0) followed by a significant decrease (APC=-7.4), and Myelodysplastic Syndromes (APC=16.4) only in the first period. Over the years, a significant increase was observed in 5-year RS for Hodgkin -, Marginal Zone -, Follicular - and Diffuse Large B-cell-Lymphomas, MPN, and Acute Myeloid Leukemia. The availability of dedicated software made it possible to recover 80% of cases automatically: the remaining 20% required direct consultation of medical records. Conclusions The study emphasizes that HM registration needs to collect information from multiple sources. The digitalization of CRs is necessary to increase their efficiency.